Usability and development of English oral toolkit with intelligent voice recognition for early age children - Aruna Govindasamy (2018)
This study aims to test the usability of English Oral Toolkit (EOT) with intelligent voicerecognition for children 3 to 6 years old. English might be a popular language to learn, but thisdoesn't necessarily mean it is a simple language to master. The fear of talking orpronouncing words wrongly becomes a major problem for using the language frequently. EOT withintelligent voice recognition developed as a teaching and learning aids using Addie model as adevelopment model. Selected 30 preschools in Seberang Prai District has been monitored to analysemethod of teaching and learning process in English language being carried out. Questionnaires andinterviews been conducted on selected 30 preschools teachers and 15 preschool students as a sampleand the results used to collect data on the usability of learning kit that been developed.Results of analysis are discussed using descriptive analysis. Overall, the ease of use of EOTand EOT usefulness was at a high level of mean which is 4.27 and 4.35 respectively. The implicationof this study found that the developed kit can enhance the understanding of childrens towardspronunciations of words in selected theme and voice recognition feature available will help earlyage children to learn proper pronunciations and rectify wrong pronunciations on selected theme.From the results its known that EOT achieved its intended objectives and able to help early agechildren to learn proper pronunciations of daily used words.